Business Ethics in Fintech and Missappropriation of Donation Funds: A Case Study of Kitabisa.com Crowdfunding Platform - Tondoyekti, Kukuh; Mariana; Arviciena Sakti, Reza; Novia Irianti, Nana (Universitas Indo Global Mandiri, 2024)
The misuse of funds on the Kitabisa.com crowdfunding platform highlights major challenges in maintaining public trust, accountability, and business ethics within Indonesia’s fintech ecosystem. While the platform has facilitated social solidarity by connecting donors and recipients, cases of fund misuse indicate gaps in governance and oversight. This issue is particularly significant given the increasing popularity of crowdfunding-based fintech in Indonesia as part of digital financial innovation influenced by digital capitalism. This study aims to analyze the causes of fund misuse through the lenses of moral judgment, moral identity, and applicable regulations, while addressing the exploitative aspects of digital capitalism. This research employs a qualitative method with a case study approach. Data were collected through document analysis, including news articles, media reports, and academic literature. The findings reveal that weaknesses in recipients' moral judgment and moral identity, a lack of strict reporting mechanisms, and the pressures of digital capitalism are key factors contributing to fund misuse. Furthermore, Indonesia's crowdfunding regulation fails to provide adequate oversight of fund recipients, focusing more on platform operators, which opens opportunities for misuse by recipients. This study offers practical recommendations, including regulatory reinforcement, stricter sanctions, the development of moral education programs for recipients, and the integration of blockchain technology to ensure transparency. These findings are relevant for policymakers, platform developers, and the public in building a more ethical, transparent, and sustainable fintech ecosystem. Keywords: Fintech ethics, transparency, digital capitalism, morality, regulation.